1597: Bernardo de Brito Writes Down the Legend of the Abducted Moor Fatima (Transmediterranean History, 2023)
At the end of the sixteenth century, Bernardo de Brito included the legend of the Muslim Fatima in a Cistercian chronicle. At an unknown time, a village called Fátima arose in geographical proximity to the narrative, which has since grown into an important Christian pilgrimage site due to several Marian apparitions in the early twentieth century. The article first discusses the motives that prompted Bernardo de Brito to engage with the legend. Then it traces its diffuse reception, demonstrating that this reception history was occasionally subject to strong political influences.